2020
DOI: 10.7861/fhj.2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a remote clinical advice service during the COVID-19 pandemic

Abstract: Service redevelopment has taken place across the NHS in response to the COVID-19 pandemic. At North Bristol NHS Trust, six vulnerable medical staff in non-patient facing roles set up a virtual advice service called 'Ask the Medical Reg'. This service aimed to provide senior medical support to inpatient and community teams for general medical and COVID-19-related queries. Here we outline the structure of our service and present data from the first 4 weeks of operation. We describe how the service has supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…18 The important role of carers during transitions of care has been highlighted during the pandemic. 19 This was because large numbers of patients were discharged from inpatient mental health services while access to community services was limited. 20 A recent systematic review found only 12 carer involvement interventions to improve patient outcomes (e.g., readmissions) during mental health transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The important role of carers during transitions of care has been highlighted during the pandemic. 19 This was because large numbers of patients were discharged from inpatient mental health services while access to community services was limited. 20 A recent systematic review found only 12 carer involvement interventions to improve patient outcomes (e.g., readmissions) during mental health transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Having effective social support (often provided by carers) is thought to reduce the likelihood of adverse events, such as suicide postdischarge 18 . The important role of carers during transitions of care has been highlighted during the pandemic 19 . This was because large numbers of patients were discharged from inpatient mental health services while access to community services was limited 20…”
Section: Introductionmentioning
confidence: 99%
“…2 Available online at: https://msss.gouv.qc.ca/professionnels/maladies-infectieuses/ coronavirus-2019-ncov/ (accessed October 25, 2021). reliable technological tools (4)(5)(6)(7)(8)(9)(10)(11). It has been suggested that with their telemonitoring/telecare capacities and remote monitoring capabilities, telehealth platforms can provide patients with practical and timely access to care (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…reliable technological tools (4)(5)(6)(7)(8)(9)(10)(11). It has been suggested that with their telemonitoring/telecare capacities and remote monitoring capabilities, telehealth platforms can provide patients with practical and timely access to care (4)(5)(6)(7)(8)(9)(10)(11). Telehealth offers asynchronous communication, collecting and tracking data but also obtaining real-time clinical feedback that is well-suited to the remote patient monitoring process (4-12).…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation